2013
DOI: 10.3390/ijerph10127299
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Retail Outlets and Vulnerable Populations in Ontario, Canada

Abstract: Interest has been increasing in regulating the location and number of tobacco vendors as part of a comprehensive tobacco control program. The objective of this paper is to examine the distribution of tobacco outlets in a large jurisdiction, to assess: (1) whether tobacco outlets are more likely to be located in vulnerable areas; and (2) what proportion of tobacco outlets are located close to schools. Retail locations across the Province of Ontario from Ministry of Health Promotion data were linked to 2006 Cens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 27 publications
3
37
1
Order By: Relevance
“…Changes to zoning and licensing of tobacco has the possibility of reducing the number of outlets substantially 3–6. For instance, limiting the sale of tobacco within 500 m of schools would have the effect of reducing the number of outlets by over 60% in Ontario 15. This study adds to the growing literature demonstrating an effect of tobacco retail availability and the potential of restrictions on availability as an effective tobacco control intervention.…”
Section: Public Health Implicationsmentioning
confidence: 81%
“…Changes to zoning and licensing of tobacco has the possibility of reducing the number of outlets substantially 3–6. For instance, limiting the sale of tobacco within 500 m of schools would have the effect of reducing the number of outlets by over 60% in Ontario 15. This study adds to the growing literature demonstrating an effect of tobacco retail availability and the potential of restrictions on availability as an effective tobacco control intervention.…”
Section: Public Health Implicationsmentioning
confidence: 81%
“…In addition, the sight of smokers gathering in proximity to retailers could trigger contagion or normalisation effects 18. High retailer counts may be more specifically indicative of a more price-competitive market, as well as of smoking being more socially acceptable as a practice,7 48 while proximity lowers the travel costs of smoking 49. These putative mechanisms linking tobacco retailer availability and smoking have mostly been discussed with regard to residential and school neighbourhoods, but they could also be at play in other settings, as individuals go about their daily activities 19 23…”
Section: Discussionmentioning
confidence: 99%
“…One avenue of promising population-level tobacco control intervention lies in targeting contextual features such as tobacco retailer availability,6 defined as the degree of convenience in obtaining tobacco products, which is affected by the number and location of retailers 6 7. The density of tobacco retailers around home8–10 or school11 12 has been associated with a higher likelihood of smoking in youth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies have shown that tobacco outlet density tends to be highest in lower socioeconomic neighborhoods or areas, resulting in a signifi cant issue of health equity [8,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%